CYTOTOXIC AND ANTI-VIRAL ACTIVITY OF Acacia catechu ON HUMAN PERIPHERAL BLOOD MONONUCLEAR CELLS - Gupta, Amit; Chaphalkar, Sushama R. (Indonesian Journal of Pharmacy, 2016)
As per the literature, medicinal plants showed enormous candidates who is responsible or showing anti-microbial, anti-cancer, anti-diabetic, anti-inflammatory agents etc. Most of the research group focused only on those primary and secondary metabolites extracted from different medicinal plants and showed its antimicrobial (anti-viral) activity against dreadful pathogens. The objective of our current study is to evaluate the cytotoxic and anti-viral effect of aqueous leaves extract of Acacia catechu against new castle disease Virus (NDV) on human peripheral blood mononuclear cells (PBMC). For these studies, variable doses of aqueous leaves extract of Acacia catechu (0.5–30mg/mL, 50µL; dissolved in phosphate buffered saline, PBS) and examined its proliferation assay containing NDV and also determined CD14 monocyte surface marker in presence or absence of NDV using flow cytometry. The results showed that aqueous leaves extract of Acacia catechu inhibited NDV proliferation and also decline in CD14 monocyte surface marker with or without NDV at higher doses. Overall, aqueous extract of Acacia catechu at higher doses showed cytotoxic as well as antiviral effect and might be used for this purpose.